2015
DOI: 10.1007/s00384-015-2423-3
|View full text |Cite
|
Sign up to set email alerts
|

CT imaging for prediction of complications and recurrence in acute uncomplicated diverticulitis

Abstract: No CT findings that could predict complications or recurrence were found. A weakness in the initial assessment of the CT scans to detect extraluminal gas and abscess was found but, despite this, the majority of patients recovered without antibiotics. This further supports the non-antibiotic strategy in uncomplicated diverticulitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 16 publications
1
26
0
2
Order By: Relevance
“…That being said, a recent re‐evaluation by Thorisson et al . of the CT imaging in the RCT by Chabok et al . has demonstrated that 7% of the CT scans had missed complications such as abscess or free air.…”
Section: Discussionmentioning
confidence: 99%
“…That being said, a recent re‐evaluation by Thorisson et al . of the CT imaging in the RCT by Chabok et al . has demonstrated that 7% of the CT scans had missed complications such as abscess or free air.…”
Section: Discussionmentioning
confidence: 99%
“…There is little evidence, however, whether pericolic or free air alone is an indication for exploration or not. If extraluminal air is used as a surrogate marker for abdominal exploration, there are five retrospective and three prospective cohort studies with a total of 1470 patients [89][90][91][111][112][113][114][115]. Most of the studies are of poor quality with a low number of patients (Data S4; 4.1).…”
Section: Should a High-fibre Diet Be Recommended Following An Episodementioning
confidence: 99%
“…Only one previous study assessed CT imaging-based predictive factors for the progression of uncomplicated diverticulitis into complicated diverticulitis [8]. In that study, only four uncomplicated diverticulitis patients progressed into complicated diverticulitis or needed emergency surgery within 1 year.…”
Section: Discussionmentioning
confidence: 99%